2021
DOI: 10.1101/2021.03.06.434216
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spontaneously Hypertensive Rat substrains show differences in premorbid addiction vulnerability traits and cocaine self-administration: Implications for a novel rat reduced complexity cross

Abstract: Forward genetic mapping of F2 crosses between closely related substrains of inbred rodents - referred to as a reduced complexity cross (RCC) - is a relatively new strategy for accelerating the pace of gene discovery for complex traits, such as drug addiction. RCCs to date were generated in mice, but rats are thought to be optimal for addiction genetic studies. Based on past literature, one inbred Spontaneously Hypertensive Rat substrain, SHR/NCrl, is predicted to exhibit a distinct behavioral profile as it rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…(ii) In addition to establishing a method for operant oxycodone intake, we sought to estimate the heritability of behavioral traits associated with voluntary oxycodone intake in rats, in order to establish the feasibility of genetic mapping studies. In line with many studies in rodents, 42–45 we estimated heritability in only one sex. We previously reported that estimates of heritability for nicotine intake are similar between males and females, 22,46 even when nicotine SA was conducted using two different methods; this suggested that genetic influences on drug taking behavior were shared between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) In addition to establishing a method for operant oxycodone intake, we sought to estimate the heritability of behavioral traits associated with voluntary oxycodone intake in rats, in order to establish the feasibility of genetic mapping studies. In line with many studies in rodents, 42–45 we estimated heritability in only one sex. We previously reported that estimates of heritability for nicotine intake are similar between males and females, 22,46 even when nicotine SA was conducted using two different methods; this suggested that genetic influences on drug taking behavior were shared between males and females.…”
Section: Discussionmentioning
confidence: 99%